Molecular and Serological Evaluation of Occult Hepatitis B Virus Infection among Patients Undergoing Maintenance Hemodialysis at a Tertiary Teaching Hospital of Bangladesh (Bangladesh Journal of Medical Microbiology, 2026)
Background: Occult hepatitis B virus infection (OBI) represents a silent yet significant phase of chronic HBV infection (CHB), characterized by the presence of HBV DNA in the liver and/or serum without detectable hepatitis B surface antigen (HBsAg). It may occur in both seropositive and seronegative individuals and poses a risk of transmission via blood transfusion, organ transplantation, and hemodialysis. Immunocompromised patients, particularly those with chronic kidney disease (CKD) undergoing maintenance hemodialysis (MHD), are particularly vulnerable due to repeated transfusions, invasive procedures, and altered immune responses.Objective: The purpose of the present study was to determine the prevalence and serological patterns of OBI among CKD patients receiving MHD at Chittagong Medical College Hospital (CMCH), Bangladesh.Methodology: This cross-sectional study was conducted from January to December 2024 in the Department of Microbiology at Chittagong Medical College, Chattogram, Bangladesh including 176 CKD patients on MHD who were HBsAg-negative, as confirmed by ELISA. HBsAg was rechecked using immunochromatographic tests (ICT). Anti-HBc and anti-HBs antibodies were detected by enzyme-linked immunosorbent assay (ELISA). HBV DNA was quantified using real-time polymerase chain reaction (qPCR).Results: All patients were negative for HBsAg. Anti-HBc was positive in 53 (30.11%) and anti-HBs in 96 (54.55%) patients. HBV DNA was detected in 6 patients (3.41%), confirming occult hepatitis B virus infection. Among them, 4 (2.27%) were seropositive and 2 (1.14%) were seronegative OBI. No significant associations were observed between occult hepatitis B virus infection status and sociodemographic variables, dialysis duration, blood transfusion history, or serological profile.Conclusion: Integration of HBV DNA testing into routine screening protocols is essential for early detection, improved clinical management, and reduction of HBV transmission risks in dialysis units.Bangladesh Journal of Medical Microbiology, July 2025;19 (2):115-120